First they came for the Young Communists: police facilitation and control at COP26, Glasgow - Gorringe, Hugo (Policing and society, 2024)
The COP26 Climate Summit held in Glasgow in November 2021 was expected to attract mass protests. Given the climate crisis and the increase in direct action in the UK, the police anticipated huge numbers with the potential for significant disorder. Despite this, Police Scotland insisted that they were committed to facilitating peaceful protest. Drawing on ethnographic observation and interviews with both police and protestors, this paper offers analysis of a contentious event during the large set-piece demonstration on Saturday 6 November. It focuses on the containment of a small group of Young Communists to ask what this tells us about ‘facilitation’, crowd theory, and police-protestor relations. Whilst fairly insignificant in terms of numbers, we argue that the YCL containment offers valuable insights into protest policing and facilitation.